Evaporative heat loss in Bos taurus: Do different cattle breeds cope with heat stress in the same way? - Franco Pereira, Alfredo Manuel; Titto, Evaldo L.; Infante, Paulo; Titto, Cristiane G.; Geraldo, Ana M.; Alves, Alexandre; Leme, Thays M.; Baccari, Flavio [UNESP]; Almeida, Jose A. (Elsevier B.V., 2014)
The aim of this study was to compare two Portuguese (Alentejana and Mertolenga) and two exotic (Frisian and Limousine) cattle breeds in terms of the relationship between the increase in ambient temperature and the responses of the evaporative heat loss pathways and the effects on homeothermy. In the experiment, six heifers of the Alentejana, Frisian, and Mertolenga breeds and four heifers of the Limousine breed were used. The animals were placed in four temperature levels, the first one under thermoneutral conditions and the other ones with increase levels of thermal stress. When submitted to severe heat stress, the Frisian developed high thermal tachypnea (125 mov/min) and moderate sweating rates (117 g m(-2) h(-1)), which did not prevent an increase in the rectal temperature (from 38.4 degrees C to 40.0 degrees C). Moderate increases in rectal temperature were observed in the Alentejana (from 38.8 degrees C to 39.4 degrees C) and Limousine (from 38.6 degrees C to 39.4 degrees C), especially in the period of highest heat stress. The Limousine showed moderate levels of tachypnea (101 mov/min) while showing the lowest sweating rates. The Alentejana showed significant increases in sweating rate (156 g m(2) h(-1)) that played a major role in homeothermy. The Mertolenga showed a superior stability of body temperature, even in the period of highest heat stress (from 38.5 degrees C to 39.1 degrees C). Uncommonly, the maintenance of homeothermy during moderate heat stress was achieved primarily by intense tachypnea (122 mov/min). The sweating rate remained abnormally low under conditions of moderate heat stress, rising significantly (110 g m(-2) h(-1)) without evidence of stabilization, only when tendency for heat storage occurred. This unusual response of the evaporative heat loss pathways infers a different thermoregulatory strategy, suggesting a different adaptation to semi-arid environment and strong association with water metabolism. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Heat stress; Respiratory frequency; Sweating rate; Bos taurus